Trend of COVID-19 cases and health sector response in Nepal - Dhimal, Meghnath; Neupane, Tamanna; Adhikari, Samir Kumar; Gyanwali, Pradip (Applied Science and Technology Annals, 2020)
We are facing global pandemic of novel corona virus diseases COVID-19 which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This paper is aimed to assess trend of COVID-19 cases and health sector response in Nepal. We reviewed WHO databases to observe the global trends and epidemiology of COVID-19 as well as daily situation updated reports of Health Emergency and Operation Centre (HEOC), guidelines, national and international government documents. The first case of COVID was reported in Nepal on 23 January 2020 and number of cases reached 454 on 21 May 2020. In order to address the increasing number of cases of COVID-19, Government of Nepal is adopting various preventive measures like extending lockdown period, setting up quarantine and isolation facilities, sealing borders, suspending flights, closing public places etc. There is need of joint effort by individuals, communities and government to prevent the further spread and flatten epidemic curve in Nepal.